Production and characterization of monoclonal antibody to duck IL-2 - GONG Hui; WU Jian-xiang; WANG Jin-yong; CHEN Ji-gang; ZHOU Ji-yong (浙江大学学报. 农业与生命科学版, 2004)
Five hybridoma cell lines secreting monoclonal antibody (mAb) against duck IL-2 were produced by fusing mouse myeloma cells (SP2/0) with spleen cells from BALB/c immunized with the purified recombinant duck IL-2 protein and named as 1H4, 2B3, 4G12, 5F6 and 5H6. One of the five hybridoma cell lines (5H6) could also react with chicken IL-2. The titres of ascitic fluids of the five mAbs ranged from 1∶32000 to 1∶512000 by indirect ELISA. Among the five mAbs, 5H6 belongs to IgG2a, and the other mAbs were of the same isotype of murine antibodies IgG1, according to the Mouse Immunoglobulin Standard Panel. The five murine antibodies' light chain hold the same isotype, κ. Western-blot analysis showed that the five mAbs could react with duck IL-2, they are supposed to against continuous determinants of duck IL-2.